Outcome Measurement in Interprofessional Education and Collaborative Practice for Tuberculosis Care in Indonesia - Ardyansyah, Bau Dilam (Curtin University, 2024)
The thesis aims to develop high-quality and reliable outcome measures to assess the impact of an interprofessional education program on health students and practitioners in Australia and Indonesia. The thesis is also a pioneering effort to evaluate interprofessional tuberculosis care on patient health outcomes, laying the groundwork for future research and quality improvement initiatives. The expected contributions have significant implications for healthcare education and practice and potentially enhance the quality of patient care.